Pengaruh Penambahan Minyak Jagung pada Pembuatan Keju Olahan (Sliced Cheese) dengan Koagulan Getah Pepaya Kering Terhadap Kadar Lemak, Daya Leleh, dan Intensitas Warna - Pratiwi, Fadila Rahma Dinda; Putranto, Wendry Setiyadi; Wulandari, Eka (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sliced cheese in general is square shape, thin, easily broken, and pale yellow color. Making sliced cheese begins with coagulation using the papain enzyme from dried papaya latex. The papain enzyme is a proteolytic enzyme that is used as an alternative replacement for the rennin enzyme because it is cheap and easy to find. The addition of corn oil to produce a better product. This research aims to determine the effect of corn oil concentration on fat content, meltability, and color intensity. This research was carried out in March 2024 at the Laboratory of Animal Product Processing Technology and Laboratory of Research and Biotechnology Testing, Faculty of Animal Husbandry, Padjadjaran University. The method used was experimentally with Completely Randomized Design (CRD) with 4 treatments adding corn oil, consisting of P1 (0%), P2 (5%), P3 (10%), and P3 (15%). Each treatment was repeated 5 times. The results showed that the addition of corn oil has a significant effect (P<0.05) on fat content. However, it had no significant effect (P>0.05) on meltability and color intensity. The best concentration is P3 with the addition of corn oil 15% which produces a fat content of 48.8%, meltability of 0.38 cm, color L* 83.03, color a* -2.63, and color b* 16.16.